CRITICAL ANALYSIS OF VALUE CHAIN: A CASE OF MANGO PROCESSING VARIETIES IN CHITTOOR DISTRICT OF ANDHRA PRADESH - R. BINDU SOWMYA *, N. T. KRISHNA KISHORE, T. LAKSHMI; SHAIK NAFEEZ UMAR (The Journal of Research ANGRAU, 2022)
In India, Andhra Pradesh leads in the area under mango with 14.72%, while Uttar Pradesh leads in production of mango with 23.47% with highest productivity, followed by Andhra Pradesh with 22.63% i.e., 4.6 million tonnes, and then Karnataka, Bihar, Gujarat, Tamil Nadu, Odisha, West Bengal, Jharkhand, and Maharashtra. In Andhra Pradesh, Chittoor district contributes production of 15.5 lakh tonnes covering 1.12 lakh ha.Of these 26000 ha have table variety mango trees such as Benishan (Banginapalle), Neelum, Dashehari, Kesar, Himayath etc. While 86000 ha have the Totapuri mango variety, which is mainly used by the industry to make pulp. The industry is concentrated in Chittoor district and is a main hub for the export of mango pulp to different nations. (APEDA, 2022).Value chain refers to “the set of actors (private, public, and service providers) and the sequence of value-adding activities involved in moving a product from production to the final consumer,” in agriculture they can be thought as is a “farm to fork” set of processes and flows. Farmers, input suppliers, private traders, processors, exporters, and consumers are all a part ofmango value chain. (Nandika and Jayasree, 2017). As a result, the following objectives were set for the research:to identify major actors and their roles, and major constraints faced by them in value chain of mango, and mapping and analysing the agri value chains for major mango varieties grown in Chittoor (Rekha Priyadarshini, 2015).